Father Absence in Long-Distance Marriage and Early Childhood Self-Confidence in Indonesia: A Qualitative Phenomenological Study Integrating Attachment and Ecological Systems Theory - Novianti, Ria; Nafisa Putri, Ainama; Maria, Ilga; Mpolomoka, Daniel (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This study examines how father absence within long-distance marriage (LDM) arrangements influences the development of children’s self-confidence, with particular attention to gender-specific vulnerabilities. The analysis is framed through an integrated perspective combining attachment theory and ecological systems theory to explain how relational and contextual factors shape children’s socio-emotional outcomes. Design/methods/approach – Employing a qualitative phenomenological design, this study involved eight participants (five mothers and three early childhood teachers) from Pekanbaru City, Riau Province, Indonesia. Data were collected through semi-structured interviews and analyzed by applying bracketing, extracting meaning units, clustering meanings, and synthesizing the essence of participants’ lived experiences through iterative verification against the transcripts.Findings – Three principal findings emerged. First, fathers in LDM arrangements were described as having lower parenting self-efficacy and often delegated daily caregiving to mothers. Second, children in LDM families were reported to show lower self-confidence, expressed through clinginess, fearfulness, and heightened anxiety consistent with disrupted attachment-related security. Third, participants’ accounts suggested gendered patterns: girls were more often described as insecure and sometimes compensatorily self-reliant, whereas boys were more often described as showing reduced confidence alongside externalizing behaviors such as aggression.Research implications/limitations – The findings extend Western father-absence literature by validating these theories within the Indonesian context, demonstrating that virtual presence (video calls, periodic visits) maintains emotional connection but cannot fully support the consistent responsiveness required for secure attachment development.Practical implications – Policy and intervention programs should focus on strengthening paternal self-efficacy and increasing the quality and frequency of father–child interactions despite geographical separation. Family education initiatives, school-based guidance services, and accessible mental health support should address qualitative relational dimensions that promote attachment security and children’s self-confidence.Originality/value – This study uniquely examines LDM-induced father absence in Indonesia, distinguishing structural absence from relational abandonment, and demonstrating that extended family support, though culturally significant, provides only partial compensation for paternal absence in early childhood development.Paper Type Research paper